2018
DOI: 10.1364/josaa.35.000577
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the orthogonal and non-orthogonal coupled-mode theory for parallel optical waveguide couplers

Abstract: The coupled-mode theory (CMT) is a powerful approach routinely used to calculate the effects of spatial mode interactions in perturbed structures, such as optical waveguides. One of its basic hypotheses requires that perturbations are weak. This is usually not the case for devices fabricated with modern semiconductor-based technologies. In this paper, the CMT is studied in these critical cases to assess its validity. Attention will be focused on the quite common case of parallel coupled waveguides. For these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, the CMT is only suitable for lossless guided modes. For a high-loss mode like a plasmonic mode, crosstalk is estimated from the normalized coupling length L c /L ave , [56,57] where L ave is the mean L p of the Sym and Asym modes, and n sym and n asym in L c [55] are the real parts of effective refractive indices. Based on the estimation of L c /L ave , one can calculate the maximum transfer power P max [56] from one channel to the other due to limited L p .…”
Section: Spectral Response and Waveguide Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CMT is only suitable for lossless guided modes. For a high-loss mode like a plasmonic mode, crosstalk is estimated from the normalized coupling length L c /L ave , [56,57] where L ave is the mean L p of the Sym and Asym modes, and n sym and n asym in L c [55] are the real parts of effective refractive indices. Based on the estimation of L c /L ave , one can calculate the maximum transfer power P max [56] from one channel to the other due to limited L p .…”
Section: Spectral Response and Waveguide Crosstalkmentioning
confidence: 99%
“…Moreover, we analyze the fraction of energy density in the slot waveguide versus tSiO2 as shown in Figure 8e. Based on the coupled mode theory (CMT), [ 55 ] the maximum mode coupling occurs in the condition that each of the constituted modes shares the same fraction (from 50% to 50%) of energy density. As a result, the strength of mode coupling between the C m and S n modes can be quantitatively described by the fraction of energy density in slot waveguide.…”
Section: Dependence Of Mode Properties On Geometric and Materials Par...mentioning
confidence: 99%
“…Optical waveguide coupling is widely employed in optical wave steering [11][12][13][14], pure optical switches [15,16], directional couplers [17], and frequency-selective filters [18,19]. The theoretical research and exploration of other applications of waveguide coupling in optics have continued unabated [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the supermode theory is applied to the analysis of the MSC [20][21][22][23][24][25][26][27]. It is shown that all characteristic parameters of the MSC can be obtained using only the propagation constants of the supermodes supported by the MSC structure.…”
Section: Introductionmentioning
confidence: 99%